The Learning Experience: Utilizing the Werewolf Game to Mitigate Speaking Anxiety Among EFL Learners - Moh Iqbal Alibi, Jaftiyatur Rohaniyah, Rini Listyowati, Arisandi Setiyawan (Journal of Educational Studies, 2025)
Speaking anxiety is a pervasive affective barrier that significantly impedes oral communication development among Indonesian EFL learners. This qualitative case study explores the implementation of the Werewolf game as a pedagogical intervention to address English-speaking anxiety. It examines students' perceptions of their learning experience in the game. Drawing on Communicative Language Teaching (CLT) and Game-Based Learning (GBL) as theoretical frameworks, the study was conducted in a speaking classroom at the Islamic University of Madura, involving 28 second-semester students across four game sessions. Data were collected through non-participant observation and semi-structured interviews with ten purposively selected participants, then analyzed using thematic analysis. The findings reveal that the Werewolf game was successfully implemented through a gradual language policy and simplified game mechanics, with initial challenges diminishing by the second session. Thematic analysis of interview data yielded five key themes: (1) perceived reduction of speaking anxiety across all participants regardless of initial anxiety levels; (2) a shift in focus from language accuracy to game goals as the primary mechanism of anxiety reduction; (3) enhanced social bonding as a buffer against fear of negative evaluation; (4) the English-only rule as a double-edged sword, beneficial for proficient students but challenging for lower-proficiency learners; and (5) contrasting preferences for game versus regular class activities, with the majority preferring the game format. The study concludes that the Werewolf game, as a GBL-CLT intervention, effectively reduces speaking anxiety by reframing speaking as a tool for achieving game goals rather than a performance to be evaluated. These findings offer practical implications for EFL teachers seeking innovative, low-anxiety instructional strategies and contribute qualitative, emic evidence to the growing literature on game-based language learning.